Self-reported and objective sleep measures in stroke survivors with incomplete motor recovery at the chronic stage - Fleming, MK; Smejka, T; Henderson Slater, D; Chiu, EG; Demeyere, N; Johansen-Berg, H (SAGE Publications, 2021)
Background: Stroke survivors commonly complain of difficulty sleeping. Poor sleep is associated with reduced quality of life and more understanding of long-term consequences of stroke on sleep is needed.